2023
DOI: 10.1038/s41590-023-01559-1
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term retention of antigens in germinal centers is controlled by the spatial organization of the follicular dendritic cell network

Abstract: Germinal centers (GCs) require sustained availability of antigens to promote antibody affinity maturation against pathogens and vaccines. A key source of antigens for GC B cells are immune complexes (ICs) displayed on follicular dendritic cells (FDCs). Here we show that FDC spatial organization regulates antigen dynamics in the GC. We identify the existence of a broader FDC heterogeneity within the network. While the entire light zone (LZ) FDC network captures ICs initially, only the central cells of the netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…IL-4 production is preserved in late-stage GC ( 46 , 47 ). Antigen is abundantly available at the start of the GC response and is preserved late into the GC response by central light zone follicular dendritic cells ( 48 ). CD40 signaling is essential for GC maintenance throughout the GC response ( 49 ).…”
Section: Identification Of Il-21 As a Key Regulator Of Humoral Immunitymentioning
confidence: 99%
“…IL-4 production is preserved in late-stage GC ( 46 , 47 ). Antigen is abundantly available at the start of the GC response and is preserved late into the GC response by central light zone follicular dendritic cells ( 48 ). CD40 signaling is essential for GC maintenance throughout the GC response ( 49 ).…”
Section: Identification Of Il-21 As a Key Regulator Of Humoral Immunitymentioning
confidence: 99%
“…These B cells can divide at a much faster rate at an endothermic core body temperature, and so the selective environment becomes increasingly segregated from the wider pool of non-specific clones. Further, only the FDCs at the center of the LZ act as a long-term reservoir of intact antigen in mice ( 134 ). Thus, it appears that the distinct microanatomical structure of the GC intensifies selection pressures by increasing competition for antigen and T cell help, thereby facilitating faster, more efficient selection of higher affinity antigen-specific B cells in endotherms.…”
Section: No Time For Slow Selection—why Did Endotherms Evolve Germina...mentioning
confidence: 99%
“…Expression of complement receptor 2 (CR2) by non-hematopoietic cells, most likely FDCs, appears to be particularly important for trapping immune complexes in the GC and maintaining high IgG antibody titers ( Fang et al, 1998 ). Indeed, a recent study by Martínez-Riaño et al (2023) showed that the topology of CR2 expression in the FDC network of mouse LNs controls antigen retention. Recording of the long-term dynamics of antigen retention in LNs of mice immunized with fluorescent immune complexes and their replacement upon reimmunization revealed that the entire FDC network contributes to initial antigen capture.…”
Section: Conserved Frc Niche Functions Across Lymphoid Organsmentioning
confidence: 99%
“…Recording of the long-term dynamics of antigen retention in LNs of mice immunized with fluorescent immune complexes and their replacement upon reimmunization revealed that the entire FDC network contributes to initial antigen capture. However, only the central FDCs in the LZ retained antigen and served as long-term antigen reservoirs ( Martínez-Riaño et al, 2023 ). It appears that high concentration or repeated antigen exposure leads to dynamic competition of immune complexes for CR2 ( Martínez-Riaño et al, 2023 ).…”
Section: Conserved Frc Niche Functions Across Lymphoid Organsmentioning
confidence: 99%
See 1 more Smart Citation